2018
DOI: 10.1002/bip.23074
|View full text |Cite
|
Sign up to set email alerts
|

Esculentin‐1a derived peptides kill Pseudomonas aeruginosa biofilm on soft contact lenses and retain antibacterial activity upon immobilization to the lens surface

Abstract: Contact lens (CL) wear is a risk factor for development of microbial keratitis, a vision threatening infection of the eye. Adverse events associated with colonization of lenses, especially by the multi-drug resistant and biofilm forming bacterium Pseudomonas aeruginosa remain a major safety issue. Therefore, novel strategies and compounds to reduce the onset of CL-associated ocular infections are needed. Recently, the activity of the frog skin-derived antimicrobial peptide Esc(1-21) and its diastereomer Esc(1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Antimicrobial peptides (AMPs) are a class of peptides, components of innate immune system, with a broad activity against bacteria, virus, fungus and more, providing a non-specific defense against a broad spectrum of invaders [110]. Recently, numerous studies [111,112] refer its use as antimicrobial loading agents for their excellent characteristics, presenting several advantages over classic antibiotics, namely fast and broad spectrum of action with low susceptibility to induce bacterial resistance [113]. In contrast with the mechanisms of action of antibiotics, which are based in slow processes of enzymatic inhibition and target specific cellular activities as DNA or protein, the AMPs are effective against different species of microorganisms and also reduce the risk of resistance development [113][114][115].…”
Section: Loading Antimicrobial Compounds Into Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial peptides (AMPs) are a class of peptides, components of innate immune system, with a broad activity against bacteria, virus, fungus and more, providing a non-specific defense against a broad spectrum of invaders [110]. Recently, numerous studies [111,112] refer its use as antimicrobial loading agents for their excellent characteristics, presenting several advantages over classic antibiotics, namely fast and broad spectrum of action with low susceptibility to induce bacterial resistance [113]. In contrast with the mechanisms of action of antibiotics, which are based in slow processes of enzymatic inhibition and target specific cellular activities as DNA or protein, the AMPs are effective against different species of microorganisms and also reduce the risk of resistance development [113][114][115].…”
Section: Loading Antimicrobial Compounds Into Materialsmentioning
confidence: 99%
“…In a recent study, Casciaro et al [111] successfully covalently immobilized frog skin derived AMP on contact lenses. This strategy not only reduced the adhesion of P. aeruginosa, a species highly associated with contact lenses associated keratitis, but it also proved to be nontoxic to mammalian cells and it did not compromise the lenses physical properties.…”
Section: By Coatingmentioning
confidence: 99%
“…AMP coated CL is the most promising one among them, due to the AMPs excellent antibiofilm activities against mature or immature biofilms (Dosler & Karaaslan, 2014). Casciaro et al (2018) have demonstrated that the frog skin AMP Esculentin-1a derived peptides represented encouraging candidates to be developed as ophthalmic formulations and/or for the manufacturing an antimicrobial CLs in order to prevent them from infections.…”
Section: Discussionmentioning
confidence: 99%
“… AMPs Surface/Devices Antimicrobial activity Ref. Esc(1–21) Contact lens Disrupt the bacterial biofilm Reduce the number of bacterial cells within 20 min and bacterial adhesion to the CL surface (77%–97% reduction) in 24 h [ 237 ] RRWRIVVIRVRRC Catheter The antimicrobial peptide coating prevented both Gram-positive and Gram-negative bacterial adhesion by up to 99.9% and inhibited planktonic bacterial growth by up to 70%. In vivo , the peptide coating was tested in a mouse urinary catheter infection model.…”
Section: Amps and Other Health Care Applicationsmentioning
confidence: 99%